Programa “Conta Pra Mim”: análise semiolinguística dos imaginários sóciodiscursivos generificados das crianças nas obras de poesia - Nicomedes, Lorraine Caroline (2024)
This dissertation investigates the discursive productions that underpin the conceptions of early childhood education, with a specific focus on the gendering pedagogical devices present in the family literacy project, proposed by the National Literacy Program (PNA) of the Ministry of Education (MEC), Programa “Conta pra Mim” (Brasil, 2019). The general objective of the work is to investigate the gendered impositions of sociodiscursive imaginaries that, through their psychosociolinguistic constitution, implicitly dictate what the female child and the male child should be like. In this context, it seeks to relate aspects of the “Conta pra Mim” Program with the historical expectations of the social ideal of childhood and with elements of the sociodiscursive imaginaries of childhood. In addition, there is the specific objective of identifying and describing gendered performativities. To assimilate the intentionality in the communicational situation between the sender and the recipient present in the works, poems were selected, including songs, parlendas, and quadrinhas. For the analysis of discursive meaning, the linguistic and situational components will be considered, in addition to relying on the operations of meaning of the verbal material and the psychosocial material, as elucidated by Charaudeau (2014). In this sense, the meaning of the discourse privileges the relationship established between the partners of the language act, without ignoring the propositional content that refers to the reference to the world, but subordinating it to the intersubjectivity of the interlocutors. Keywords: Semiolinguistics. Childhood. Gendering.